Recent findings of Isthmohyla pictipes (Anura: Hylidae) in Costa Rica: variation and implications for conservation - Chaves-Acuña, Wagner; Chaves, Gerardo; Klank, Jeremy; Arias, Erick; Bolaños, Federico; Shepack, Alex; Leenders, Twan; Cossel, John; Faivovich, Julián (Zootaxa, 2020)
We report recent findings of Isthmohyla pictipes (Cope, 1875) in the Cordillera de Talamanca, Costa Rica, roughly two decades after it was last registered. We provide notes on microhabitat use, color variation, external morphology of adults and larvae, and geographic variation, and discuss some taxonomic characters employed to differentiate I. pictipes from I. tica (Starrett, 1966) and I. xanthosticta (Duellman, 1968). We also report fluorescence on the ventral surfaces of I. pictipes. Our findings are expected to shed light on the taxonomy of this species and should be useful in further population assessments and conservation plans.